The effects of mountain reservoir operations on the distributions and dispersal mechanisms of riparian plants, Colorado Front Range - Merritt, David M., author; Wohl, Ellen E., advisor; Chapman, Phillip L., committee member; Laituri, Melinda J., committee member; Friedman, Jonathan, committee member (Colorado State University. Libraries, 1999)
Many factors interact to determine the composition and successional dynamics of riparian plant communities. The colonization of newly created sites along river corridors and the addition of species into existing communities are limited by the dispersal of seeds. seed germination, and seedling survival. Water dispersal (hydrochory) is an important means of both short- and long-distance dispersal of seeds along riparian corridors. Interruptions in any phase of dispersal (primary or secondary dispersal or deposition) of a particular species are likely to influence the structure of plant populations. Dams affect dispersal of riparian plant propagules through: (1) modifying hydrologic regimes and hydraulics, affecting the dynamics of seed transport and deposition. (2) altering the temporal availability and suitability of streamside habitat through controlling river stage, and (3) imposing a barrier to the downstream movement of seeds and vegetative propagules. The purpose of this investigation was to develop an understanding of the influence of fluvial landforms and modified flow regimes on the dispersal and deposition of the seeds of riparian plants through a series of flume and field experiments. Seeds were deposited non-randomly under all simulated flow regimes in flume experiments with the exception of the most rapid rate of drawdown (ramped hydrologic regime), which resulted in dispersal of seeds over a broad elevational gradient. Higher concentrations of seeds were deposited under stepped and gradually descending drawdowns, than under ascending and ramped hydrologic regimes. Early and late dispersing seeds were deposited in greater numbers than seeds released at intermediate times under descending and stepped regimes. Late dispersing species were favored under ascending flows and early dispersing species were favored under ramped regimes. Shape of the drawdown curve as well as timing of seed release determine the concentrations of seeds deposited along shorelines. Relative velocity (V/Vmx). which is an index of the strength of recirculating flow. explained a significant proportion (91%) of the variability in deposition of early dispersed seeds, indicating that seeds are deposited in the highest concentrations immediately below constrictions to flow. in zones of strong flow recirculation. and in slackwater areas adjacent to constrictions. Reynolds number. Froude number. and Weber number associated with flow fields at each fluvial feature explained as much as 75, 83, and 75 percent of the variability in seed deposition under the stepped regime. respectively. Field measurements indicated that the seed density as well as species richness of the hydrochoric seed bank were depleted below reservoirs along two high gradient streams in Colorado. suggesting that reservoirs are effective traps for water-dispersed seeds. Hydrochoric species comprised from between 12 and 25 percent of riparian vegetation at these sites. whereas wind- and water-dispersed species comprised from 41 to 55 percent of the floras. Relationships between dispersal phenology, patterns of wind and water dispersal. and standing vegetation were quantified using a non-parametric measure of concordance (Kendall's W). The composition of wind-dispersed seed rain was found to vary as a function of local-scale factors such as site species composition. Species composition of hydrochoric seeds was less related to local- and reach-scale community composition upstream of reservoirs, but was highly related to standing vegetation below reservoirs. This suggests that seeds may be derived from sources throughout the watershed upstream from reservoirs, but that hydrochoric seeds are depleted and richness is 'reset' below dams. This fragmenting may have long-term implications for the structure of vegetation downstream from dams, and effects may become more evident with time since impoundment.
Keywords: ecology; botany